2021
DOI: 10.1080/23744235.2021.1882697
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the eye: a review

Abstract: Background: To provide a review for general practitioners and medical specialists about the most common eye complaints and ocular manifestations in a COVID-19 patient. Methods: Reviewed 50 articles referenced in 4 databases from 20 December 2019 to 16 September 2020. Results: Of the 50 articles reviewed, 26 met the criteria for analysis and were included in the study. Among them were 5 reviews, 6 case series, 7 case reports, 4 cross-sectional studies, 2 systematic reviews, 1 cohort study and 1 correspondence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Vision abnormalities have been reported in clinical practice by several COVID-19 and post-COVID individuals, including sore eyes and light sensitivity [73,74]. Despite the possible influence of acute SARS-CoV-2 infection and hospitalization on ocular manifestations described in this sample, none of the participants reported eye complaints (e.g., acute conjunctivitis) during the acute phase of the disease, and an ANS involvement might be suspected.…”
Section: Discussionmentioning
confidence: 60%
“…Vision abnormalities have been reported in clinical practice by several COVID-19 and post-COVID individuals, including sore eyes and light sensitivity [73,74]. Despite the possible influence of acute SARS-CoV-2 infection and hospitalization on ocular manifestations described in this sample, none of the participants reported eye complaints (e.g., acute conjunctivitis) during the acute phase of the disease, and an ANS involvement might be suspected.…”
Section: Discussionmentioning
confidence: 60%
“…Vision disturbances may also occur in Long-COVID syndromes including sore eyes and light sensitivity [ 119 ]. In acute conjunctivitis, an abnormal pupil response has been noted [ 120 ].…”
Section: Neurocardiologic Involvementmentioning
confidence: 99%
“…These manifestations are usually seen in severe diseases accompanying systemic signs and abnormal blood parameters [ 30 32 ]. In several review papers, the frequency of various ophthalmic presentations was reported to be low (from 0 to 31.58%) [ 20 , 22 , 33 ], and in three meta-analysis studies, the calculated frequency was almost 11% [ 34 36 ]. Variability in reported rates between studies could be due to the confounding effect of unobserved factors [ 37 ].…”
Section: Resultsmentioning
confidence: 99%